(NwSE L@DI (B- (NWRAGI(B: [(NrOMAN(B] / s (N~ASTX (B3s - (NoLDINGTON(B, (NrI^ARDs ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1989)
(Nw TOM TRETIJ ^ETYREHTOMNOGO sOBRANIQ SO^INENIJ rI^ARDA oLDINGTONA (B(1892-1962) (NWHODIT IZWESTNYJ ROMAN (B"(NwSE L@DI (B- (NWRAGI(B", (NPOWESTWU@]IJ O SUDXBE PREDSTAWITELQ (B"(NPOTERQNNOGO POKOLENIQ(B".s
rus
Keywords: (NpSIHOLOGI^ESKIJ ROMANs